Pulmonary hypertension in chronic lung diseases: comparison to other pulmonary hypertension groups. (1st June 2018) - Chebib, Nader; Mornex, Jean‐François; Traclet, Julie; Philit, François; Khouatra, Chahera; Zeghmar, Sabrina; Turquier, Ségolène; Cottin, Vincent
Abstract : Group 3 pulmonary hypertension (PH) is a common complication of advanced chronic lung disease. Our hypothesis was that group 3 PH is associated with a more severe baseline presentation and a more severe prognosis compared to group 1 pulmonary arterial hypertension (PAH), chronic thromboembolic PH (group 4), and group 5 PH. We retrospectively analyzed consecutive incident PH patients in a single center between January 2006 and November 2014. Data were acquired from a prospective database. Clinical, functional, and hemodynamic characteristics, as well as survival, were compared between the four groups of precapillary PH. A total of 363 patients were analyzed; 164 patients (45.2%) belonged to group 1 PAH, 109 (30%) to group 3 PH, 65 (17.9%) to group 4 PH, and 25 (6.9%) to group 5 PH. Group 3 patients were predominantly male and were more frequently in New York Heart Association (NYHA) class III/IV. Patients with group 3 and 4 PH were older, had significantly lower 6‐min walking distance (6MWD), higher mean pulmonary arterial pressure, higher pulmonary vascular resistance (PVR), and lower cardiac index (CI) than PAH patients. Group 3 and 5 patients had significantly lower total lung capacity (TLC), forced vital capacity (FVC), and FEV1; group 3 patients had the lowest carbon monoxide transfer coefficient values. PH therapy was used in 90.9% of group 3 patients. Univariate analysis of prognostic factors in the overall population showed that age, male gender, NYHA class, groups 3 and 4 PH (vs. PAH), 6MWD, FVC, TLC, carbon monoxide transfer coefficient (KCO), PVR, CI, and venous oxygen saturation were significantly associated with greater mortality. Multivariate analysis showed that age, PH group 4, 6MWD, and KCO but no longer PH group 3 were significantly associated with mortality. Patients with group 3 PH are older, have more severe baseline presentation and lower survival rates than PAH patients in univariate analysis, that seemed to be related to older age.